Practical aspects of conservative urinary incontinence treatment in everyday general practitioner practice - Surkont, Grzegorz; Wlaźlak, Edyta (Przewodnik Lekarza/Guide for GPs, 2006)
Most women suffering from urinary incontinence do not need specialized management. Conservative treatment should be more often applied in the everyday practice of first line physicians and regional gynaecologists. Only in cases of failure should patients be sent for specialized management in out-patient clinics: urogynaecologic, gynaecologic and urologic. The authors also indicate situations where the patient at the first stage should be sent for specialized management.